The dipeptidyl peptidase IV inhibitor vildagliptin suppresses development of neuropathy in diabetic rodents: effects on peripheral sensory nerve function, structure and molecular changes. Issue 4 (11th January 2016) - Tsuboi, Kentaro; Mizukami, Hiroki; Inaba, Wataru; Baba, Masayuki; Yagihashi, Soroku
Abstract: Incretin‐related therapy was found to be beneficial for experimental diabetic neuropathy, but its mechanism is obscure. The purpose of this study is to explore the mechanism through which dipeptidyl peptidase IV inhibitor, vildagliptin (VG), influences neuropathy in diabetic rodents. To this end, non‐obese type 2 diabetic Goto‐Kakizaki rats (GK) and streptozotocin (STZ)‐induced diabetic mice were treated with VG orally. Neuropathy was evaluated by nerve conduction velocity (NCV) in both GK and STZ‐diabetic mice, whereas calcitonin‐gene‐related peptide expressions, neuronal cell size of dorsal root ganglion (DRG) and intraepidermal nerve fiber density were examined in GK. DRG from GK and STZ‐diabetic mice served for the analyses of GLP‐1 and insulin signaling. As results, VG treatment improved glucose intolerance and increased serum insulin and GLP‐1 in GK accompanied by the amelioration of delayed NCV and neuronal atrophy, reduced calcitonin‐gene‐related peptide expressions and intraepidermal nerve fiber density. Diet restriction alone did not significantly influence these measures. Impaired GLP‐1 signals such as cAMP response element binding protein, protein kinase B/Akt (PKB/Akt) and S6RP in DRG of GK were restored in VG‐treated group, but the effect was equivocal in diet‐treated GK. Concurrently, decreased phosphorylation of insulin receptor substrate 2 in GK was corrected by VG treatment. Consistent with the effect on GK, VG treatment improved NCV in diabetic mice without influence on hyperglycemia. DRG of VG‐treated diabetic mice were characterized by correction of GLP‐1 signals and insulin receptor substrate 2 phosphorylation without effects on insulin receptor β expression. The results suggest close association of neuropathy development with impaired signaling of insulin and GLP‐1 in diabetic rodents. Diabetic neurons are resistant to insulin and such insulin resistance may contribute to development of neuropathy. DPP‐IV inhibitor, vildagliptin, corrected insulin resistance and improved neuropathy irrespective of blood glucose via augmented action of GLP‐1. Abstract : Diabetic neurons are resistant to insulin and such insulin resistance may contribute to development of neuropathy. DPP‐IV inhibitor, vildagliptin, corrected insulin resistance and improved neuropathy irrespective of blood glucose via augmented action of GLP‐1.